PENERAPAN HUKUM PIDANA TERHADAP TINDAK PIDANA PEMBELIAN BARANG CURIAN MELALUI MEDIA SOSIAL - ANDI AKHMAD ARAFAH; Soekarno Aburaerah; Abdul Agis (Qawanin Jurnal Ilmu Hukum, 2020)
The birth of social media with complete technological facilities allows its users to communicate with other users who are far away, but as if they are in close proximity. Social media has also played a lot in the fields of economy and trade with its ability to support product marketing activities to buying and selling activities. In a buying and selling transaction of goods, the Indonesian people sometimes or most of the buyers are interested in goods that are sold at below market prices. But sometimes the desire to get the difference or profit, if not careful, can get the buyer into criminal law problems. Article 480 of the Criminal Code regarding help (evil) or what in criminal practice is known as the article of heling (heling). This is what motivates the author to take the title "Enforcement of the Application of Criminal Law Against the Crime of Purchasing Stolen Goods Through Social Media" Based on the background of the problems above, the problem formulation in this thesis is as follows: 1. What are the factors that lead to the criminal act of purchasing stolen goods on social media, 2 What are the efforts to implement the applicable law against the purchase of stolen goods through social media? The research method uses qualitative, while the types used in this study are primary and secondary data. qualitative approach data analysis technique, which is a research procedure that produces descriptive data, which is stated by the related parties in writing or verbally and real behavior, which is researched and studied is a complete research object, as long as it is something real. The results of this study conclude that the factors driving the purchase of stolen goods are the price of the item is below the market price or a very low price, the letters are incomplete, the time to sell the goods is not on time (at night), the transaction is carried out in secret, and the conditions abnormal or defective items. If the above elements are fulfilled, the person who acts on these elements can be subject to detention because the person has fulfilled all the elements of the criminal detention above. And the application of the law stipulates that the actions committed by the defendant must be held accountable to him, so that it can provide a deterrent effect and in the future do not do the same thing. The legal consequence for the perpetrator of detention crime is that the perpetrator receives a criminal sanction in accordance with Article 480 of the Criminal Code.